Comparability of an innovative Doppler ultrasound fetal heart rate monitor to a pinard fetal stethoscope using cardiotocography as a standard to assess the fetal heart rate in singleton pregnancies during labour at Mowbray Maternity Hospital - Chinula, Lameck (Department of Obstetrics and Gynaecology, 2014)
Includes abstract.